Plaque volume, composition, and fraction versus ischemia and outcomes in patients with coronary artery disease - Kuneman Jurrien H.; van den Hoogen Inge J.; Schultz Jussi; Maaniitty Teemu; van Rosendael Alexander R.; Kamperidis Vasileios; de Graaf Michiel A.; Broersen Alexander; Jukema J. Wouter; Bax Jeroen J.; Saraste Antti; Knuuti Juhani (Elsevier Inc., 2025)
Background
The various plaque components have been associated with ischemia and outcomes in patients with coronary artery disease (CAD). The main goal of this analysis was to test the hypothesis that, at patient level, the fraction of non-calcified plaque volume (PV) of total PV is associated with ischemia and outcomes in patients with CAD. This ratio could be a simple and clinically useful parameter, if predicting outcomes.
Methods
Consecutive patients with suspected CAD undergoing coronary computed tomography angiography with selective positron emission tomography perfusion imaging were selected. Plaque components were quantitatively analyzed at patient level. The fraction of various plaque components were expressed as percentage of total PV and examined among patients with non-obstructive CAD, suspected stenosis with normal perfusion, and those with reduced myocardial perfusion. Clinical outcomes included all-cause mortality and myocardial infarction.
Results
In total, 494 patients (age 63 ​± ​9 years, 55% male) were included. Total PV and all plaque components were significantly larger in patients with reduced myocardial perfusion compared to patients with normal perfusion and those with non-obstructive CAD. During follow-up 35 events occurred. Patients with any plaque component ​≥ ​median showed worse outcomes (log-rank p ​< ​0.001 for all). In addition, low-attenuation plaque ​≥ ​median was associated with worse outcomes independent of total PV (adjusted HR: 2.754, 95% CI: 1.022–7.0419, p ​= ​0.045). The fractions of the various plaque components were not associated with outcomes.
Conclusion
Larger total PV or any plaque component at patient level are associated with abnormal myocardial perfusion and adverse events. The various plaque components as fraction of total PV lack additional prognostic value.